Timing and reasons behind single-sport specialization in soccer: A survey of 64 Major League Soccer athletes - Knapik, D. M.; Rizzone, K. H.; Voos, J. E. (Sports Health: A Multidisciplinary Approach, 2020)
Background: Single-sport specialization at the exclusion of other sports has become increasingly popular in youth sporting culture. The purpose of this study was to survey Major League Soccer (MLS) athletes to examine factors influencing the timing of single-sport specialization in soccer.